Empowering Bioentrepreneurship through the Utilization of Rambutan Peel Active Compounds as Hand Sanitizer - Kelsha Berliana Rifty; Bryan Verdhatama (Jurnal Bisnis dan Kewirausahaan, 2026)
The underutilization of rambutan (Nephelium lappaceum L.) peel waste presents a significant opportunity for bioentrepreneurship. This project bridges biotechnology and business by transforming agricultural waste into a high-value, natural hand sanitizer. Utilizing the potent antibacterial properties of active compounds specifically tannins, flavonoids, and geraniin the extraction process employs a maceration method with food-grade solvents to ensure safety and efficacy.Preliminary results demonstrate that these phytochemicals effectively inhibit bacterial growth, offering a non-toxic and eco-friendly alternative to synthetic, high-alcohol sanitizers. From an entrepreneurial perspective, this innovation leverages low-cost raw materials to reduce production costs while meeting the rising market demand for sustainable hygiene products. Ultimately, this initiative serves as a catalyst for local bioentrepreneurship, promoting a circular economy by converting organic waste into a marketable bioproduct that provides both scientific and sustainable health solutions.